Guardians of the night - Russell, Alan 1956- (Seattle Thomas & Mercer, 2015)
As the sole members of LAPD's Special Cases Unit, Detective Michael Gideon and his German shepherd partner Sirius work investigations considered bizarre even by Los Angeles's standards. Yet their latest case is more than strange -- it might be out of this world. Ronald "Wrong" Pauley is a homeless man long fallen from grace. When Pauley's late-night drinking is interrupted by a detonation of light, he sees what he describes as a "being of light" in the alley below. Pauley tries to help, but ends up as a witness to what he believes is the murder of the fallen angel. Gideon and Sirius are already in the midst of trying to determine the identity of the so-called "Reluctant Hero" who seemed to magically appear just moments after shots began ringing out at an elementary school. Braving gunfire, the hero tackled the shooter, and then disappeared. Both cases defy easy answers, but when Pauley turns up dead, the detectives are left with two murders to solve and lots of questions. Gideon and Sirius -- along with help from a newfound friend--investigate that thin line between the real and surreal to make sense of these possible crimes. In this exciting and captivating sequel to Burning Man, a smart-mouthed skeptic and his loyal partner must unravel a dark otherworldly mystery to deliver real-world justice
1
Keywords: Los Angeles (Calif.) -- Police Department -- Fiction; Los Angeles (Calif.) -- Police Department; Homeless men -- Fiction; Homeless men; Murder -- Investigation -- Fiction; Murder -- Investigation; Police dogs -- Fiction; Police dogs; Police -- Fiction; Police; California -- Los Angeles; Los Angeles (Calif.) -- Fiction; Fiction; Mystery fiction